AN ANALYSIS OF HEALTH CONDITION OF WOMEN BEEDI ROLLERS IN TELANGANA STATE (International Journal of Food and Nutritional Sciences, 2022)
Beedi rollers, primarily Telugu workers in India, make up 76% of employment, with 90%-95% operating from home. However, the sector often aids in financial exploitation of women labor, with intermediaries hiring women with subpar tendu leaves. Beedi production facilities are mostly in Maharashtra's Aurangabad, Solapur, and Nanded, with no set working hours. Telanagana State, India, is a major tobacco producer and a significant contributor to rural economic growth. Beedi rolling employs a large workforce, accounting for 14.4% of all employment in the unorganised sector and 1.1% in the state. The state has over ten beedi manufacturing businesses, with Karimnagar being the most employed district Beedi rollers, who number 7 lakh in the state, are disproportionately prevalent in the northern districts. Beedi rolling, a labor-intensive, back-breaking occupation in Telangana, is particularly beneficial for women and children who have lost their husbands to drunkenness.